A 3D‐Printed, Sensitive, Stable, and Flexible Piezoresistive Sensor for Health Monitoring. Issue 10 (29th July 2021) - Ma, Lijun; Xia, Tiancheng; Yu, Rui; Lei, Xiao; Yuan, Jun; Li, Xiaotian; Cheng, Gary J.; Liu, Feng
Abstract : The flexible piezoresistive sensors have great potentials in wearable electronics. Sensitivity and stability are the key parameters for the piezoresistive sensors. However, the 3D flexible piezoresistive sensors are difficult to meet high sensitivity and good stability simultaneously. Herein, combining 3D printing with a carbon nanotubes (CNTs) surface‐filled (SF) structure that CNTs are filled in the surface of styrene–ethylene–butylene–styrene (SEBS) substrate, a highly sensitive, stable, and flexible piezoresistive sensor is developed. Experimental results show that the CNTs SF sensor not only has high sensitivity similar to the CNTs surface‐coated sensor, but also has good stability similar to the CNTs integral‐filled sensor. Due to the 3D network structure and SF CNTs conductive layer, the sensor shows high stretchability of 20.9 times, good sensitivity of 161.53 kPa −1 at an applied pressure <250 Pa under compressed status, high gauge factor of 7.24 under stretched status, excellent stability (>2000 cycles), the short mechanical response time (149 ms) and recovery time (75 ms). Meantime, the sensor shows an obvious response to temperature. Furthermore, the sensor is used to detect tiny and big human activities such as speaking, throat swallowing, and breathing, exhibiting its great potential for application in wearable electronics. Abstract : A highly sensitive, stable, and flexible piezoresistive sensor is developed by combining three‐dimensional printing with a carbon nanotubes surface‐filled structure. The sensor shows high stretchability, good sensitivity, high gauge factor, excellent stability, the short mechanical response time, and recovery time. Meantime, the sensor shows an obvious response to temperature. Furthermore, the sensor has great potential for application in wearable electronics.